OFR-68-83 Preliminary Predictive Model Of Subsidence Process Over Room And Pillar Workings - Phase I: Definition Of Factors - S. K. Mathur (The National Institute for Occupational Safety and Health (NIOSH), 1982)
This report identifies all the possible activities, variables and factors that contribute to the surface subsidence process over room and pillar workings. These factors are responsible for mine instability and collapse that ultimately transforms into surface subsidence. Such a failure mechanism is initiated by the failure of the mine floor bed and or the failure of the pillars or the failure of the roof after second mining, which eventually brings down the roof. The individual responses of the pillar, floor and roof rocks to the mining induced stresses and the complex interaction between these components can't be attributable to any single factor. Also, no attempt has been made to quantify the significance of each of these factors and relate to the ground subsidence due to the lack of field data. The discussion here is centered primarily on the first mining though second mining is mentioned very briefly,